Undercover - Kephart, Beth. (New York : HarperTeen, 2007)
High school sophomore Elisa is used to observing and going unnoticed except when classmates ask her to write love notes for them, but a teacher's recognition of her talent, a "client's" desire for her friendship, a love of ice skating, and her parents' marital problems draw her out of herself.
"Laura Geringer books.".
Young Adult
Keywords: Family problems -- Fiction; High schools -- Fiction; Ice skating -- Fiction; Letters -- Fiction; Love-letters -- Fiction; Poetry -- Fiction; Schools -- Fiction; Family life -- Fiction; High schools -- Fiction; Ice skating -- Fiction; Letters -- Fiction; Poetry -- Fiction; School stories